Vestibular Barre Syndrome and Lieou - Aniya, Julio (1963)
Barré syndrome and Lieou of vestibular origin, is characterized by a vertiginous symptomatology box , accompanied by disorders of neuro- vegetative type ; which is often confused with Meniere's Syndrome and other neurolóciccs entities. The cause of this condition lies in a cervical disc disease at C5- C6 level of understanding that phenomena on the sympathetic peri -arterial -cervical vertebral artery disorders will produce reflections at the maze , preferably ; or of the vestibular nuclei . The only way to make the diagnosis , is practicing a systematic exploration labyrinthine and proper interpretation of the signs found in the exploration of patients carrying the above mentioned sintomotoloqia and that its records have certain signs that indicate commitment to the spine ; in the cervical segment. Confirmation of the diagnosis is obtained by radiographic examination of the cervical spine in which injuries are the type of disc disease between 5th . & 6th . vertebrae , arthritis or bone injuries. In all patients we have presented , five in number , found the following vestibular signs : positional vertigo accompanied by headache ; disturbance of vestibular function type gradient of reflectivity ; position nystagmus Rase position; harmonic segmental deviations; , neuro - vegetative dystonia variable degree between 5th cervical disc disease . & 6th . vertebrae, with different levels and confirmed by radiographic examination . As any signs we found spontaneous nystagmus in 2 cases , lateralizaciones in locomotor test in 4 cases. Found commitment elbow type of light perceptive hearing loss, with varying profiles and the guy in the " plateau " predominates. Of all these signs found in the vestibular examination , we conceptualize of great value in this syndrome ( Barré syndrome and Lieou ) the occurrence of positional nystagmus (Hose position) , which is usually accompanied by autonomic manifestations of type ( 4 cases) such as nausea , vomiting and fainting in some cases , which would be explained by irritation of the cervical sympathetic to get in hyperextension cervical spine . In all cases studied , have been classified as peripheral , endolaberíntico , global type labyrinthine syndrome, which possibly indicates a reflex disturbance in the hydrodynamics of endolymph , roughly similar to the one presented in Meniere's syndrome , which occur in this case maybe , by repeated engioespásticos phenomena , the labyrinthine arteries. We performed a symptom - therapeutic trial basing ourselves on the concept just mentioned (C9 ) with excellent results for the jugular vertiginous crisis. Despite the large number of scans performed both vestibular Service ORL Loayza Archbishop Hospital, as well as private clients ; we have found only five cases and Lieou Barré syndrome , which are the only ones described in our midst. Nevertheless, we regard to be ' more often this entity , given the large percentage of carriers of cervical disc disease . We suggest Vestibular systematized scans in patients with cervical disc disease presenting vertiginous symptoms.